MINAT BELAJAR SISWA DALAM PENGGUNAAN HERBARIUM BOOK SEBAGAI MEDIA PEMBELAJARAN DI SMPN 1 CIMAUNG - Muhammad Bambang Jundi Firdaus, - (2020)
This research was motivated by the appropriate cases at SMPN 1 Cimaung in science subjects in the learning process of plant material due to the lack of concrete in understanding the learning material. Organization for Economic Co-operation and Development (OECD) proves that students' understanding of science lessons is still lacking due to the facilities, facilities and learning media. Biology learning media in the form of a herbarium is a concrete example of learning media from preserved dry specimens of plants. The purpose of this research was to see students' interest in learning in using herbarium books at SMPN 1 Cimaung. This research method uses descriptive research using survey methods. Participants in this study were 45 students of class IX of SMPN 1 Cimaung. The instruments used were questionnaires, documentation study, and instrument development. Simple random sampling technique. The analysis technique used is the percentage descriptive data analysis and the Chi-square test. Based on the research conclusions can be drawn: 1) Student interest in learning using herbarium book learning media is very positive, that student interest in learning is higher using herbarium books; 2) The practicality of using the herbarium book as a science learning media in the classification and boundaries of plants at SMPN 1 Cimaung practical dictionary; 3) Obstacles that helped students while using the herbarium book at SMPN 1 Cimaung included inadequate understanding of the material if it was not accompanied by a teacher, incomplete data in the herbarium book; 4) Students' efforts to overcome obstacles to using herbarium books, including sharing plant information with other colleagues, asking the teacher about related specimens, inviting friends to discuss and creating small discussion groups